Addressing distributor profitability in the fast-moving consumer goods industry - Lagrisola, Ralph Ranil A. (Animo Repository, 2021)
The purpose of this action research is to create a cost-saving distribution model that would both help Mondelez and partner distributors achieve the goals and objectives in sales and distribution while maintaining sustainable profitability. By using first; second; and third person inquiry, I and the collaborators were able to successfully pilot two distribution models that are less costly, without compromising meeting the target KPIs of the company. This is made possible by the action research proper where the process serves as a guide toward a more efficient and effective approach to the change management process, the use of the PDCA framework, and the handling of powerful conversations to resolve issues along the way. Two series of action research cycles for the project were conducted. The major shift was to convert pre-selling operations to drop sell operations. The first focused on a hybrid distribution model, using one truck instead of two trucks to save on fleet costs and manpower, while activating sales representatives as sellers through their motorcycles. For the second cycle, three-wheeled vehicles were utilized considering that such are more economical to operate, can saturate narrow roads, and can maximize the advantage of drop selling versus the current pre-selling model. Given the pilot run, we encountered few issues, still, through usage of the principles of the action research process, we were able to adjust, achieve, and even surpass the goals set at the start of the project. Lastly, I reflected on the entirety of the project – focusing on the content, the process undertaken, and the knowledge acquired as a result of doing the action research at the organization level. In the end, an extrapolation to a larger context was considered consequently due to the learnings acquired. Keywords: profitability, fast moving consumer goods, modern kaizen, PDAC, route to market, distribution, viability, retail channel, operating costs, net income, cost efficiency